Efeitos de projetos lean: um estudo das divergências entre as percepções contábil e de produção em empresas industriais dos setores metal-mecânico e elétrico do estado do RS - Herrera, Ana Lucia Schenkel (Universidade do Vale do Rio dos Sinos, 2017)
The divergences between the perceptions, from accounting and production, regarding the effects of lean projects may conceal or even lead the company to abandon the benefits made through this approach. The manner economic results are accounted for can encourage the company to prioritize projects that bring economic results in the short term and discourage others that have operating benefits not reflected in accounting indicators but that present incremental and long-term results. The study proposed in this master's thesis analyzes how companies measure the effects of continuous improvement projects based on lean manufacturing. The research is qualitative, based on data analysis in four serial production companies of the medium-sized and large metal-mechanical and electrical industrial sectors, and that carry out projects of continuous improvement through lean principles, based on semi-structured interviews with those responsible for continuous improvement programs and those responsible for measuring project results in the respective companies, and non-participating observation. Evidence indicates that these companies prioritize projects that deliver economic results and on the other hand, different ways of demonstrating benefits or the possibility of avoiding future costs are created when they are not accounted for. Evidence of knowledge regarding cost flow through value was identified in three of the four companies interviewed. However, only one of them has planned to implement lean accounting and migrate accounting to align with the production system. The relationships between variables relevant to the problem were also analyzed, producing a systemic map which may contribute to support future studies on this subject.
Keywords: Lean manufacturing; Lean accounting; Contabilidade de gestão; Management accounting; ACCNPQ::Engenharias::Engenharia de Produção